Tingkat Toleransi Beragama Siswa SMA: Survei pada Siswa Muslim di SMA Negeri Kota Cimahi - Maitsaa Rifani Khoirunnisa; Munawar Rahmat; Saepul Anwar (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Senior high school students are the most vulnerable group to be infiltrated by radicalism. In order to prevent it, tolerance is included into the 18 values of Indonesian character education that need to be internalized in Indonesian students. This study aims to explore the level of religious tolerance among Muslim students in senior high school, as the majority religion, especially in the aspects of faith and muamalah. This research was a descriptive research with a quantitative approach using a Cross-Sectional Survey. The research was conducted in all the state senior high schools in Cimahi City with 707 respondents. Respondents were given a closed questionnaire using a Likert scale. The results showed that in general, 92.94% of state high school students in the city of Cimahi have a fairly good tendency towards religious tolerance; even 289 (40.88%) students were in the 'very high' category. However, there are still a small number of students who have a low level of tolerance, namely 48 (6.79%) students and it was very unfortunate that 2 (0.28%) students were detected as intolerant. The conclusion is the level of religious tolerance of Muslim students at state senior high schools in Cimahi City is already quite good, but it needs to be improved.